A strategy using mesoporous polymer nanospheres as nanocarriers of Bcl-2 siRNA towards breast cancer therapy. Issue 3 (20th December 2018) - Wu, Xin; Zheng, Yawen; Yang, Dan; Chen, Taijun; Feng, Bo; Weng, Jie; Wang, Jianxin; Zhang, Kai; Zhang, Xingdong
Abstract : Synthesis and functionalization of a novel therapeutic nanoplatform available for cancer therapy. Abstract : Small interference RNA (siRNA) has demonstrated unprecedented potential as a therapy for drug-resistant cancer. However, efficient cellular delivery is still a challenge due to hydrolytic sensitivity and poor cellular uptake of siRNA. Strategies to conjugate siRNA to the delivery vehicle and activate innate immunity have shown low in vivo efficacy. Therefore, nanomedicine approaches have become the main focus in this field. B-cell lymphoma 2 (Bcl-2) is the founding member of the Bcl-2 family of regulatory proteins that regulate cell death (apoptosis), by either inducing (pro-apoptotic) or inhibiting (anti-apoptotic) apoptosis. In this report, a nanomedicine system is constructed using Bcl-2 siRNA as the therapeutic agent and mesoporous polymer nanosphere (MPN) carriers to both improve cellular internalization and achieve Bcl-2 silencing and cell apoptosis. MPNs were prepared through a two-stage hydrothermal process at two different temperatures, which was deliberately designed to form nanospheres via self-assembly and create mesoporous structures by removing the pore-forming templates. Such MPNs were proved to be biodegradable. Without any carbonization process, MPNs still keep many active groups which endow them with excellent properties for functionalization purposes. Finally, the FA-targeted-Bcl-2-siRNA-loaded nanoparticles were constructed by a layer-by-layer assembly by electrostatic interactions after nitrification. These nanoparticles were efficiently delivered into breast cancer (BC) cells, showing a significant sequence-specific inhibition of Bcl-2 mRNA expression in BC cells, enhanced tumor cell apoptosis and tumor therapeutic efficacy. Taken together, this study establishes a novel therapeutic system for cancer therapy.